Juridical Studies Concerning Punishment Against Elderly - ., Fatriansyah (2018)
Rule criminal can be laid against the offender aged prevailing at this time is the form of imprisonment. The imposition of imprisonment, it is not effective when viewed from the achievement of the nature of the criminal prosecution and achievement of the goals of the law. Judging from the nature of punishment, imprisonment can only achieve retributive of punishment that retaliation against criminal acts committed by a lawbreaker, but imprisonment is not able to achieve the goal of preventive so others deterrent perform the same actions and objectives rehabilitative or recovery the offender so that he realized his mistake and constructed such that in time, he can get back into society as citizens who obey the law. Meanwhile when viewed from the purpose of law, the imposition of imprisonment against perpetrators of criminal acts elderly are also ineffective. Although able to meet the achievement of the principles of justice and the legal certainty the imposition of imprisonment does not have the legal expediency. Conception renewal of criminal law may be filed relating to the setting of punishment against the perpetrators of the crime of aging is to adopt the provisions of the Criminal Code concerning the reduction of crime and alternative sentencing such that the obtained setting punishment against perpetrators of criminal acts elderly are able to meet the objectives of the law and the objective of sentencing in effective. Keywords:: Punishment, Elderly